Riba in The Perspective of Sharia Bank Customers: A Systematic Literature Review - Ahmad Hasan Asy'ari Ulama'i; Ferida Rahmawati; Maaz Ud Din (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN KH Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine the Islamic bank customers to the understanding of usury. This type of research is literature review research. The type of data collected in this study is primary data, namely data obtained from various current and relevant literature regarding the level of understanding of Islamic bank customers about usury, such as from books, journals, articles, papers, and other related reading sources. The data analysis technique of this research was carried out using the data analysis technique of the Miles and Huberman model. The data analysis activities of this model include data reduction, data display and conclusion drawing or verification. The results of a systematic literature review found that usury is an additional take, both in buying and selling transactions and lending and borrowing in vanity. The prohibition of usury in the Qur’an was revealed in stages, preceded by a series of moral teachings relevant to the theme of the prohibition of usury. Conventional banks use the interest system to support their operations. In contrast to the interest system prevailing in conventional banks, Islamic banks determine the amount of return and profit sharing based on the amount of profit sharing between the customer and the bank without determining the percentage that must be paid by the customer. Bank interest is an evolution of the concept of usury that cannot be separated from the development of financial institutions. Riba in modern banking makes business decline and become unproductive. Education and religion can be used as the basis for mu’amalah for all mankind, especially Muslims. Islamic education can lead humans to become individuals who are able to survive in this world and the hereafter (al-falah). Education about usury provides important information that can be a guide for human life in contemporary mu’amalah.